Analisis Perlakuan Akuntansi Konstruksi Pengerjaan Dalam Penyajian Laporan Keuangan pada Dinas Pekerjaan Umum Kota Gorontalo - Rahman, Zubaidah (Universitas Gorontalo, 2018)
As for the purpose of this research was to determine the Accounting Treatment of Construction In the execution of the Financial Statements in the Public Works Department of the city of Gorontalo. How Accounting Treatment Construction In the execution of the Financial Statements in the Public Works Department of the city of GorontaloBased on the results presented earlier, it was found that the acquisition of fixed assets construction in progress on the means Public Dungingi Terminal and Pump House on the balance sheet at the Public Works Department of the city of Gorontalo not comply Treatment accounting, this can be seen in table 5.3 above, which shows the value of property and equipment construction in progress, construction in progress account in 2013 as records have been adjusted in the accounting treatment of Rp 6,725,491,000.00, it has been an accumulation value acquisition fixed assets construction in progress means Dungingi and Houses Public Terminal Pompatetapi not include the costs inherent in current procurement transactions means Dungingi Public Terminal and Pump house facilities